Whole genome assembly, annotation and bioinformatics analysis of streptococcus agalactiae isolated from cow suffering of mastitis - Zubair, Saima (2012)
Streptococcus agalactiae is an obligate parasite and contagious pathogen living within the epithelial cells lining of acini of the bovine udder, causing milk disease mastitis particularly subclinical mastitis in dairy cattle. This bacterial pathogen also causes infection in pre-milking heifers, as well as neonates. We performed whole genome sequencing of strain 09mas018883 of Streptococcus agalactiae. We carried out a reference guided assembly of short paired end reads generated from Illumina Genome Analyzer II using A909 S. agalactiae strain as a reference; as a result a draft genome sequence was generarted. The length of this draft genome sequence is 2127931 bps, consisting of 2129 protein coding genes. We made a comparison of the nickel operons nikABCDE of this genome with those of few others strains of Streptococcus agalactiae to observe the genetic diversification of this region among different strains. Along with pathogenicity islands, these nickel operons might be involved in the conversion of non-pathogenic bacteria to pathogenic through horizontal gene transfer (HGT).